UPAYA PENINGKATAN MUTU PEMBELAJARAN DARING MELALUI SUPERVISI AKADEMIK GURU DI SMA NEGERI 7 DENPASAR - Cokorde Istri Mirah Kusuma Widiawati (Widyadari : Jurnal Pendidikan, 2021)
The purpose of this study was to determine whether there was an effect of academic supervision on teachers in improving their performance during a pandemic with online learning at SMA Negeri 7 Denpasar in the 2020/2021 school year. This type of research is school action research. The subjects in this study were teachers of SMA Negeri 7 Denpasar. The implementation of school action research is carried out in two cycles and in each cycle four main activities are carried out, namely: planning, acting, observing, and reflecting. Based on the results of school action research, it can be concluded as follows (1) Continuous guidance in an effort to implement the quality of online learning through teacher academic supervision can increase teacher motivation in compiling complete teaching administration and teaching planning through academic supervision so as to produce higher quality learning. (2) Academic supervision activities can improve teacher competence in preparing lesson plans which in turn improve the quality of online learning. (3) Continuous guidance can improve teacher competence in preparing lesson plans. This can be proven from the results of observations / observations which show that there is an increase in teacher competence in compiling lesson plans and online learning from cycle to cycle.